Shareholder Income Taxes and the Relation between Earnings and Returns* - DHALIWAL, DAN S.; ERICKSON, MERLE M.; LI, OLIVER ZHEN (Contemporary Accounting Research, 2005)
Abstract The purpose of this study is to investigate whether and how shareholder‐level taxes affect earnings response coefficients (ERCs). Our tests indicate that when the tax rate on dividends increases, ERCs decrease for firms with high levels of dividend yield and whose marginal investor is likely to be an individual. For firms with high levels of share repurchase yield and whose marginal investor is likely to be an individual, an increase in dividend tax rate has no discernible effect on ERCs. These results are consistent with the notion that the tax penalty on dividends, relative to capital gains, reduces the earnings‐return relation.